‘It’s the perfect storm’: why are people with eating disorders at risk of suicide? A qualitative study - Una Foye; Saakshi Kakar; Niamh McNamara; Agnieszka Musial; Tom Jewell; Jessica R. Griffiths; Carol Kan; Gerome Breen; Rachel Rowan Olive; T. Suratwala; Aman Sidhu; Lizzie Mitchell; et al. (BMC Medicine)
Abstract Background Eating disorders (EDs) are associated with elevated all-cause mortality, with suicide cited as the second leading cause of death among individuals with EDs. Evidence suggests that individuals with anorexia nervosa are 18 times, and those with bulimia nervosa seven times more likely to die by suicide, relative to gender- and age-matched comparison groups. Limited research has focused on why people with EDs experience such high rates of suicidality. The study aims to gather perspectives from people with lived experience of an ED and clinicians working with EDs to understand suicidality among people with EDs. Methods Using a qualitative design, we conducted semi-structured interviews with people with lived experience of an ED (n = 30), and clinicians who work with people with EDs (n = 19). Participants with lived experience presented with a range of EDs. Clinicians worked across a range of service settings as well as adolescent and adult services. We used a multi-perspective reflexive thematic analysis to code the data and generate the themes. Results Key themes identified include ‘no way out’: the unique role of eating disorders in suicidality across illness and recovery, the outsider experience: feeling unseen, misunderstood, and burdensome, sparks of hope: protective Factors against suicidality, and ‘they only see weight’: how gaps in ED care reinforce isolation and risk. These findings underscore the complex and multifaceted reasons why people with EDs are at risk of suicide, acknowledging the unique risk factors associated with the illness itself as well as the various risk periods that affect those with EDs. Conclusions The results are novel and illuminate psychological processes that are not currently incorporated within existing theoretical models of suicide, indicating that prevailing frameworks may lack the specificity or sensitivity required to account for the distinctive experiences of individuals with EDs. Consequently, these findings provide preliminary evidence to inform the development of a more nuanced theoretical model of suicidality specific to this population. Moreover, they suggest potential targets for intervention and highlight the need to critically evaluate treatment approaches that prioritise rapid symptom remission, which may, at times, exceed individuals’ psychological capacity to cope.